Implementation of Project-Based Learning Method to Enhance Critical Thinking Skills of Secondary School Students - Aisyah Nur Taqqiyah (Generasi Sains Indonesia, 2024)
This research paper explores the efficiency of Project-Based Learning (PBL) to improve critical thinking among the students studying at the secondary schools. In acknowledging the growing needs of teaching methods that would lead to teaching that results in higher-order thinking, this study attempts to give empirical approaches to the PBL process as a way of developing the analytical, evaluative, and reflective thinking skills in students. Data were collected using a classroom observation, semi-structured interviews with students and teachers with the method of a qualitative research design; the content of the research project output documents were also analyzed. Thematic analysis showed four major findings and included (1) active work with authentic problem-solving tasks is a trigger of increased analytical thought; (2) cooperation evokes critical reflection on the exchange of various views; (3) independence of students constitutes stimulation of responsible behavior and self-reflection learning; and (4) continuous feedback stimulates reflective thought and metacognition. This data agrees with the created literature confirming the efficacy of PBL as the tool that facilitates critical thinking and provides new-found answers specific to the Indonesian case of secondary learning. This research proposes that teachers should use a strategic approach to PBL to combine the impact of PBL with informed guidance and feedback so as to make PBL most effective in transforming the cognitive world of students. The outcome also makes clear the importance of the policies that support teacher training and curriculum implemented on the critical thinking on PBL basis.